Involvement of 5-HT2A receptor hyperfunction in the anxiety-like behavior induced by doxorubicin and cyclophosphamide combination treatment in rats - Yuka Nakamura; Yoshihisa Kitamura; Yusuke Sumiyoshi; Nanami Naito; Shiho Kan; Soichiro Ushio; Ikuko Miyazaki; Masato Asanuma; Toshiaki Sendo (Elsevier, 2018)
We examined whether combination treatment with doxorubicin and cyclophosphamide, a traditional chemotherapy for breast cancer, induced anxiety-like behavior in rats. Furthermore, we evaluated the role of the serotonin (5-HT)2A receptor subtype in the anxiety-like behavior induced by such chemotherapy. Rats were intraperitoneally injected with doxorubicin and cyclophosphamide once a week for 2 weeks. This caused the rats to display anxiety-like behavior during the light-dark test. In addition, we examined the rats' 5-HT2A receptor-mediated behavioral responses. Combination treatment with doxorubicin and cyclophosphamide significantly increased (±)-1-(2,5-dimethoxy-4-iodophenyl)-2-aminopropane, (a 5-HT2A receptor agonist)-induced wet-dog shake activity. This anxiety-like behavior was significantly inhibited by mirtazapine, a 5-HT2A receptor antagonist/5-HT1A receptor agonist, and tandospirone, a partial 5-HT1A receptor agonist, but not by fluoxetine, a selective serotonin reuptake inhibitor. The anxiety-like behavior induced by doxorubicin and cyclophosphamide combination treatment is mediated by hyperfunctioning of the 5-HT2A receptor. Thus, 5-HT2A receptor antagonists or 5-HT1A receptor agonists might be useful for treating chemotherapy-induced anxiety disorders. Keywords: Doxorubicin, Cyclophosphamide, 5-HT2A receptor, Anxiety